2-(2-methoxyethoxy)ethyl methacrylate hydrogels with gradient of cross-link density. (January 2016) - Kadlubowski, Slawomir; Matusiak, Malgorzata; Adamus, Agnieszka; Olejniczak, Magdalena N.; Kozanecki, Marcin
Abstract: Electron beam irradiation of 2-(2-methoxyethoxy)ethyl methacrylate and ethylene glycol dimethacrylate mixtures leads to the formation of cross-linked structures that exhibit a gradient of cross-link density, as demonstrated by gel fraction, swelling and Differential Scanning Calorimetry analysis. The reason for observed phase separation is formation of the high molecular weight clusters and its precipitation before gelation dose. This effect can be controlled/influenced by absorbed dose and cross-linker concentration. Highlights: Thermo-sensitive hydrogels with gradient of cross-link density. Analysis of parameters describing network formation. Synthesis of hydrogels with various morphology depending on post-irradiation procedure.